THE USE OF DIGITAL STORY IN TEACHING READING NARRATIVE TEXT FOR SMP STUDENTS - Apriltya, Rila; ., Regina; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research aims to find out the effectiveness of the digital story as media for teaching reading narrative text to the Eighth Grade Students of SMP Negeri 2 Pontianak in Academic Year 2014/2015. The research method that used is a pre-experimental and the research design that used is the one group pre-test post-test design.The sample of this research was class VIII D which consisted of 35 students. The technique of data collecting was measurement technique. The data were collected through pre-test and post test by usingthe multiple choice test which consist of 20 items.The result of data analysis showed that mean score post-test was higher than pre-test (from 60.85 to 79.28).  The computation of the effect size with the score  1.80  ( > 1.00)  shows  that  the  use  of  digital story  as  media  has  the  strongeffect in teaching reading narrative text.   Keywords: reading, narrative text, digital story.   Abstrak: Penelitian ini bertujuan untuk menemukan keefektifan dari cerita digital sebagai media untuk mengajar membaca teks narrative untuk siswa kelas dua dari SMP Negeri 2 Pontianak tahun ajaran 2014/2015. Metode penelitian yang  digunakan adalah pre-eksperimen dengan rancangan penelitian yang  digunakan adalah satu grup pre-test post-test. Sampel penelitian ini adalah kelas VIII D yang terdiri dari 35 siswa. Teknik pengumpulan data adalah teknik pengukuran. Data penelitian dikumpulkan melalui pre-test dan post-test dengan menggunakan tes pilihan ganda yang berjumlah dua puluh soal. Hasil analisis data menunjukan bahwa nilai rata-rata dari post-test lebih tinggi dari pada  pre-test (60.85-79.28).  Perhitungan dari ukuran efek dengan nilai 1,80 (>1,00)  menunjukan bahwa kegunaan dari cerita digital sebagai  media  memiliki efek  yang kuat dalam pengajaran membaca teks narative. Kata Kunci :membaca, teks naratif, cerita digital.